Investigating Factors that Generate and Maintain Variation in Migratory Orientation: A Primer for Recent and Future Work - Delmore, Kira E.; Liedvogel, Miriam (Frontiers in Behavioral Neuroscience, 2016)
The amazing accuracy of migratory orientation performance across the animal kingdom is facilitated by the use of magnetic and celestial compass systems that provide individuals with both directional and positional information. Quantitative genetics analysis of several animal systems suggests that migratory orientation has a strong genetic component. Nevertheless, the exact identity of genes controlling orientation remains largely unknown, making it difficult to obtain an accurate understanding of this fascinating behavior on the molecular level. Here we provide an overview of molecular genetic techniques employed thus far, highlight the pros and cons of various approaches, generalize results from species-specific studies whenever possible, and evaluate how far the field has come since early quantitative genetics studies. We highlight that phenotypic variation can be achieved by diversifying the expression of different component of the genetic regulatory network on various levels, and outline how future studies can take advantage of high-resolution tracking and sequencing techniques to characterize the genomic architecture of migratory orientation.